2023
DOI: 10.1590/1519-6984.268941
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of capsaicin and its analogs in vitro

Abstract: Capsaicin (CAP) is the main compound responsible for the spicy flavor of Capsicum plants. However, its application can be inhibited due to its pungency and toxicity. This study aimed to evaluate and compare the cytotoxic effect of CAP and its analogs N-benzylbutanamide (AN1), N-(3-methoxybenzyl) butanamide (AN2), N-(4-hydroxy-3-methoxybenzyl) butanamide (AN3), N-(4-hydroxy-3-methoxybenzyl) hexanamide (AN4) and N-(4-hydroxy-3-methoxybenzyl) tetradecanamide (AN5) on the hepatoma cells of Rattus norvegicus using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The Indian population consumes several-fold more chili than populations in other countries, yet this does not appear to adversely affect growth, organ weight, nitrogen balance or blood chemistry ( 93 ). Previous studies in animals and mammalian cell lines have not suggested any mutagenic effects of capsaicin in somatic cells or the germline ( 94 ). Capsaicin cream has been used in the clinic for numerous years to relieve various types of pain, and long-term local application of capsaicin can be effective for treating skin cancer in mice ( 28 , 50 , 95 – 98 ).…”
Section: Pharmacokinetics Of Capsaicinmentioning
confidence: 96%
“…The Indian population consumes several-fold more chili than populations in other countries, yet this does not appear to adversely affect growth, organ weight, nitrogen balance or blood chemistry ( 93 ). Previous studies in animals and mammalian cell lines have not suggested any mutagenic effects of capsaicin in somatic cells or the germline ( 94 ). Capsaicin cream has been used in the clinic for numerous years to relieve various types of pain, and long-term local application of capsaicin can be effective for treating skin cancer in mice ( 28 , 50 , 95 – 98 ).…”
Section: Pharmacokinetics Of Capsaicinmentioning
confidence: 96%
“…These compounds exhibit anti-inflammatory, antioxidant, immunomodulatory, and anti-tumor effects. [8][9] In this article, two new amides with an unusual (2formyl-5-hydroxymethyl)pyrroyl-butylamine moiety (1-2) were obtained from Physochlainae Radix (Figure 1). The isolation, structure elucidation were described below.…”
Section: Introductionmentioning
confidence: 99%
“…The broad applicability of capsaicin (8-methyl- N -vanillyl-6-nonenamide) and capsaicin analogues in the food, pharmacy, and health industry has led to a renewed interest in these compounds (Abdel-Salam 2014 ; Basith et al 2016 ; Santos et al 2023 ). Among the spectrum of applications, perhaps the most promising one is the apoptotic effect of capsaicin in several human cancer cell lines such as KB (Lin et al 2013 ), prostate cancer (Mori et al 2006 ), and glioblastoma cells (Lee et al 2000 ; Szoka and Palka 2020 ).…”
Section: Introductionmentioning
confidence: 99%